Pathologic response and safety to neoadjuvant PD-1 inhibitors and chemotherapy in resectable squamous non-small-cell Lung cancer - Shi, Liang; Meng, Qiyi; Tong, Li; Li, Hongxia; Dong, Yujie; Su, Chongyu; Liu, Zhe (Frontiers in Oncology, 2022)
Background Several randomized studies have shown that the combination of programmed cell death 1 (PD-1) inhibitor and chemotherapy is efficacious as a treatment for advanced non-small-cell lung cancer (NSCLC). However, in the neoadjuvant setting, there is scarce evidence of the effectiveness and safety of the combinations in squamous NSCLC. We conducted a retrospective study to evaluate neoadjuvant PD-1 inhibitor plus chemotherapy in resectable squamous NSCLC. Methods Patients from Beijing Chest Hospital, Capital Medical University, between October 2019 and October 2021, treated with PD-1 inhibitors and chemotherapy for resectable squamous NSCLC were retrospectively studied. The primary objectives were to assess the pathological tumor response and safety of neoadjuvant PD-1 inhibitors and chemotherapy. Results 63 patients with resectable squamous NSCLC stage IIA-IIIB were included. Two to four cycles of PD-1 inhibitors (37 cases with camrelizumab, 11 cases with toripalimab, 8 cases with tislelizumab, and 7 cases with sintilimab) and chemotherapy were administered prior to surgery. 42 patients (66.7%) achieved a major pathologic response (MPR), including 25 (39.7%) with a pathologic complete response (pCR). Twenty-one patients (33.3%) experienced grade 3 neoadjuvant treatment-related adverse events (TRAEs), and no patient had grade 4 or 5 TRAE. Conclusion Neoadjuvant PD-1 inhibitors and chemotherapy are feasible therapies for resectable squamous NSCLC. It was associated with a 66.7% MPR rate, 39.7% pCR rate, and tolerable toxicity.